Applying a Bayesian model incorporating discards in the assessment of four-spot megrim (Lepidorhombus boscii) Southern stock - Abad, Esther; Fernández-Llana, Carmen; Pérez-Contreras, María Nélida (2011)
Since 2003 when the DCF started at European level by countries, discards data are available for many stocks. Four-spot megrim is traditionally assessed with XSA (extended survivor analysis) which does not include discards. For this species, discards in number are very important, being around the 60% of total catch. A Bayesian model incorporating discards was realized for the hake stock in ICES Divisions VIIIc and IXa by Fernández et al. (2010). This model was also designed to produce a complete time-series of discard estimates. Final run of the model is compared with results from XSA performed in the working group of 2010, showing that mayor differences are in the fishing mortality for younger ages, being higher incorporating discards data.